Serological profile of buffalo (Bubalus bubalis) female calves vaccinated with standard Brucella abortus strain 19 vaccine using rose bengal, 2-mercaptoethanol and complement fixation tests - Nardi Junior, G. [UNESP]; Ribeiro, Márcio Garcia [UNESP]; Jorge, Andre Mendes [UNESP]; Megid, Jane [UNESP]; Silva, L. M. P. (Academic Press Ltd Elsevier B.V. Ltd, 2012)
The serological profiles of 21 female buffaloes vaccinated between 3 and 8 months of age using Brucella abortus strain 19 (S19) were evaluated by rose bengal (RBT), 2-mercaptoethanol (2ME) and complement fixation (CFT) tests. The serum strains were collected in day zero, 15, 30, 45, 60th days and subsequently to each 30 months, until 720th day after vaccination. No animal showed reaction in day zero. In 15th day above 95% of animals revealed reaction in all tests. All the animals presented absence of reactions in CFT, RBT and 2ME tests at 270, 300 and 360 days after vaccination, respectively. Our finding highlighted early response in CFT compared than other conventional agglutination tests. None of animals presented oscillation of titers or reactions in any test after 360 day of study, which enables the use of these tests after this period without interference of antibodies from S19 vaccine origin between 3 and 8 months in buffalo heifers. (c) 2011 The International Alliance for Biological Standardization. Published by Elsevier Ltd. All rights reserved.
Keywords: Brucellosis; Brucella abortus; Buffalo; Vaccination; Strain 19; Serodiagnosis